Non alcoholic fatty liver disease related hepatocellular carcinoma: A 7 years retrospective observation study - Woon, Yong Chin (2020)
NAFLD related HCC is one of the uncommon causes of HCC compare to Hepatitis B, Hepatitis C and alcoholic. Evidence of NAFLD related HCC is in rising trend in view of increase incidence of obesity and metabolic disease among population. Our aim was to study the NAFLD related HCC in one of the high volume hepatobiliary centre in Malaysia to determined its incidence, various factors associated with NAFLD related HCC and survival outcome. It’s a retrospective cross sectional study among the patient underwent liver resection in Hospital SultanahBahiyah for HCC in the period of 7 years (2009-2016). Liver resection include anatomical and non-anatomical hemihepatectomy, segmentectomy, bisegmentectomy, multiple segmentectomy, left and right hepatectomy, extended right and left hepatectomy, either in emergency or elective setting. Other surgery or procedure that is not involve in liver resection like excision or incision biopsy, FNAC of liver nodule, are excluded. This study includes demographic, comorbid, intraoperative and postoperative findings and complications, as well as survival analysis using Kaplan Meiyer and cox regression.Most patients are male (71.3%), fall between age group of 60-69 (27.9%), with weighted mostly between 65.1kg-75kg (33.1%), and BMI below 25 (82.4%). Both groups demonstrated similar characteristic features in age, weight and BMI. Comorbids are overall higher compare to viral group [DM 34 vs 17 viral group (p=0.010); Hypertension 50 vs 29 viral group (p=0.004); Dyslipidemia 19 vs 3 vital group (p=0.00); IHD 9 vs 3 vital group(p=0.095); CKD 6 vs 3 viral group (p=0.298)]. Lymphovascular involvement and local invasion were observed more in NAFLD group (42 vs 33, p=0.269; 36 vs 21, p=0.638). Operation time was longer in NAFLD group (158.2 minutes vs 143.9 minutes, p=0.176), but blood loss was more in viral group (599.8ml vs 489.7ml, p=0.648). More surgical resection of liver done for NAFLD group in compare to viral group (p=0.294). Post op complications were not significant different among two groups except HAP more in NAFLD group (23 vs 9 viral group, p=0.011), and slightly lower mortality numbers were observed in NAFLD group (29/72, 40% vs 29/64, 45%, p=0.338). Resected HAFLD HCC associated with more comorbid, and carries more post- operative complications, and lower mortality compare to resected viral HCC.